Co-delivery of antineoplastic and protein drugs by chitosan nanocapsules for a collaborative tumor treatment. (10th February 2017) - Wu, Dong-Yan; Ma, Yu; Hou, Xiao-Shuang; Zhang, Wen-Jie; Wang, Pei; Chen, Huan; Li, Bo; Zhang, Can; Ding, Ya
Highlights: Nanocapsules were prepared by amino acid derivatives of chitosan. A simple and quick emulsification method to prepare nanocapsules. A general co-delivery system for chemical drug and protein. Enhanced tumor cell inhibition and apoptosis in HeLa cells. Abstract: Although combination delivery (co-delivery) shows much superiority in the defect compensation of single-agent therapy, the construction and application of co-delivery systems are still challenging, especially for protein-based joint systems. In this work, a series of chitosan (CS)-amino acid derivatives (Arg-CS, Lys-CS, and Phe-CS) with different degrees of substitution (DS) were synthesized to prepare CS nanocapsules (CNCs) using a simple emulsification method in the presence of linoleic acid (LA). The hydrophobic drug can be loaded in LA droplets, and a positively charged protein stabilized the optimized Arg-CS nanocapsules (Arg-CNCs) on their negative surfaces. The in vitro antitumor efficacy of Arg-CNCs co-delivering paclitaxel and recombinant human caspase-3 was evaluated in HeLa cells. The co-delivery system displayed much lower IC50 values and a higher percentage of apoptotic cells compared with the control groups. This system provides a promising and universal strategy for co-delivery, leading to collaborative tumor treatment.